Application Of Conference Writing Methods Can Improve Short Story Writing Skills - Kasmidawati Kasmidawati (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. Problems to be studied in this research are: a. How to improve learning result of Indonesian language especially about writing short story? b. Steps taken in improving learning outcomes Indonesian language ?. The approach of this research uses a qualitative approach with classroom action research design, which is carried out cyclically. Cycle I with planning, action, observation, and reflection. Likewise the next cycles. In PTK as well as teachers can examine their own activities on their own done in its own class. By involving their students through planned, implemented and evaluated actions, TOD can be performed without interrupting other learning and will not burden the work of the teacher in performing daily tasks. PTK can be done in an integrated manner with daily activities. Precisely with PTK teachers can improve the quality of learning processes and products. The study considers the results or impact of classroom action research from various criteria based on reflections for revision. Reflection is a re-application of the lessons learned. The reflections are evaluations that have been made and suggestions for future learning. Based on the description of researchers draw conclusions as follows: The ability of students to write short stories in class IV before using the method of writing (writing together) is categorized enough with the average value: 6.90 (unfinished). There is an increase in the ability to write short stories with the method of writing writing (writing together) grade IV students are categorized both with an average value of 7.69 (complete). This capability increases in cycle II and cycle III reaches an average value of 8.46 (complete). Matched material for writing short story experiences for students SDN 07 Pasar Salido is a material that suits the conditions, desires, experiences, and the ability to write short stories.